The Role of Financial Literacy as A Moderating Variable in the Impact of Fintech Payments on Consumer Behavior - Litamahuputty, Jacomina Vonny; Siahaya, Agus; Cornelis, Victor (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study sought to evaluate the moderating effect of financial literacy on the influence of fintech payment on consumer behavior. To explain fintech payment using the Technology Acceptance Model (TAM), which incorporates perceived usefulness and perceived simplicity of use as independent variables. This study is an example of quantitative research. A total of 112 pupils from Politeknik Negeri Ambon were asked to complete questionnaires for this study. The sampling method employed was purposive sampling with specific criteria, which was then analyzed with Smart PLS software. This study demonstrates that perceived utility has a direct and significant influence on consumer behavior. The perception of usability has a direct and substantial effect on consumer behavior. Financial literacy as moderation is able to moderate perceived usefulness and perceived convenience of use in relation to consumption.